Sitagliptin phosphate: isolation and identification of two degradation products formed under acid conditions and determination of in vitro cytotoxicity - Lange, Alini Dall Cortivo; Miron, Diogo; Sfair, Le´tícia Lenz; Schapoval, Elfrides Eva Scherman (Drug Analytical Research, 2026)
Sitagliptin phosphate (STG), used for the treatment of type 2 diabetes, is a drug that belongs to a new class called inhibitors of dipeptidyl peptidase IV (DPPIV). It is known to be the first agent of the class approved by the FDA. Currently, many studies describe the determination of STG in plasma and pharmaceutical formulations but there are few studies on the drug stability. Forced degradation studies were conducted to isolate and identify the main degradation products. It was possible to observe the formation of two degradation products (DP1 and DP2) in hydrochloric 2.5M acid at 60°C. The structural characterization by UPLC-UV/MS of the degradation products was important to understand the degradation mechanism of STG under acid conditions. Purified degradation products were tested in vitro for cytotoxicity with a mononuclear cell assay. No cytotoxicity was observed at the concentration range of 10.0–250.0 µg.mL-1. The structural characterization of the degradation products was important to understand the degradation mechanism of STG under acid conditions. Today, there are some resolutions and consensus, national and international, which show the importance of knowing and identifying the degradation products and also to evaluate the cytotoxic potential of these molecules.